Paired Storytelling Technique Assisted with Wayang Kancil in Enhancing Democratic Attitude of Elementary Students (Journal of Primary Education, 2019)
This study aims to analyze the effectiveness of the paired storytelling technique assisted with wayang kancil to enhance democratic attitude of elementary students. The research method used is the sequential explanatory mixed-method design. The sample in this study is the fifth A and B-grade students of Public Elementary School Petompon 01 Semarang. Quantitative data were analyzed using a t-test and N-gain test based on the value of students’ democratic learning on theme Our Environment. Qualitative data were analyzed through the descriptive content of democratic concepts based on the wayang kancil storytelling ‘Demokrasi Rimbaraya’ (Democracy in the Forest). The study result shows that there were average differences of students’ democratic learning in the experimental group from the control group. The improvement of the student democratic learning in experimental group was bigger than the control group. Based on the analysis result of the story of wayang kancil there were five emerging themes: (1) mutual acceptance, (2) living together in differences, (3) respect for others, (4) responsibility, and (5) being fair. Encountering with these democratic elements through wayang kancil as medium of instruction promotes students’ understanding of democracy.